Tawassul in Hadith Perspective: Countering Heretical Rituals in Indonesia - Samsurizal, Samsurizal; Sadi, Ifteakar Mohammad; Afrianto, Afrianto; Busmayaril, Busmayaril; Ohira, Norman; Busral, Busral (Sekolah Tinggi Ilmu Tarbiyah (STIT) Ahlussunnah Bukittinggi, 2023)
Islam as a divine religion has guidance which its followers believe comes from Allah. So, this guide is known as the holy kitab in the form of the Alquran. However, there are some Muslims who engage in behavior that deviates from Islamic teachings, one form of which is the error in the tawassul ritual. This research aims to explain how to provide an antidote to rituals among people affected by the behavior of praying to pious people who have died in wrong ways or rituals according to Islamic law. This research uses a systematic literature method with a phenomenological approach, the data source comes from scientific articles that have been published in google scholar and scopus, tafsir and hadith kitab, data analysis techniques by collecting information related to tawassul and religious rituals carried out by people in Indonesia. The findings show that there are three tawassul in Islam and mistakes in the tawassul ritual by some people in Indonesia are related to the way of tawasul to someone who has died. First, tawassul includes something that is prescribed in Islam, although in practice there is disagreement among scholars. Second, tawassul includes problems with the caliphate in Islam, until there are scholars who allow and prohibit it, and third, tawassul with Asma’ al-Husna and tawassul with good deeds, the scholars agree about the Shari'at-his. The results of this research have been able to explain tawassul from the point of view of hadith that can counteract the ritual tawasul which is misguided by presenting the actuality of phenomena that have already occurred.